Adequacy of social disclosure of the open capital companies on the administration report and explanatory notes to the NBC T 15 recommendations Adequação da evidenciação social das empresas de capital aberto no relatório da administração e notas explicativas às recomendações da NBC T 15 - Ilse Maria Beuren; Marines Lucia Boff; Juliane Elisabeth Horn; Marciane Angela Horn (Revista de Contabilidade e Organizações, 2010)
The NBC T 15, approved by CFC Resolution from 1.003/04, standardizes the procedures for social and environmental information disclosure, to be followed by companies from January 1st., 2006 on. Therefore, the study aims to verify if the social disclosure on the administration report and on the explanatory notes of open capital companies is adequate to the NBC T 15 recommendations, comparing the social practice of 2005, the year before, and the social practice of 2007, the year after the implementation of such resolution. Thus, a descriptive research was carried out through documental research, with quantitative approach. There had been analyzed the administration reports and explanatory notes of the period from 2005 to 2007, of 23 open capital companies, listed on the magazine Exame 150 Melhores Empresas Para Você Trabalhar, 2007 special edition. The survey results show that, when examining the categorization of companies' social disclosure, which could be CI (complete information), II (incomplete information) or AI (absent information), the last category prevailed, using NBC T 15 as parameter. Comparing the social disclosure scores of the years 2005 and 2007, it was found that ten companies showed increase in their final score, while seven showed a decrease. Regarding to the social disclosure level of adequacy to the NBC T 15 recommendations, based on the analyses of the administration reports and explanatory notes in the period from 2005 to 2007 of the 23 open capital companies in this study, it is concluded that there is a predominance of regular classification, since four companies had insufficient disclosure qualification, twelve regular qualification, six good qualification and one company obtained great qualification. A NBC T 15, aprovada pela Resolução do CFC nº. 1.003/04, normatiza os procedimentos para evidenciação de informações de natureza social e ambiental, que devem ser observados pelas empresas desde 1º de janeiro de 2006. Assim, o estudo objetiva averiguar se a evidenciação social no relatório da administração e nas notas explicativas das empresas de capital aberto está adequada às recomendações da NBC T 15, comparando o exercício social de 2005, ano anterior, e o exercício social de 2007, ano posterior à entrada em vigor da referida norma. Para tanto, realizou-se pesquisa descritiva, por meio de pesquisa documental, com abordagem quantitativa. Analisaram-se os relatórios da administração e notas explicativas do período de 2005 a 2007, das 23 empresas de capital aberto listadas na Revista Exame 150 Melhores Empresas para Você Trabalhar, edição especial 2007. Os resultados da pesquisa mostram que, quando analisada a categorização da evidenciação social das empresas, podendo ela ser de forma completa (IC), incompleta (II) ou ausente (IA), a última categoria predominou, usando como parâmetro o preconizado na NBC T 15. Comparando-se a pontuação da evidenciação social entre o ano de 2005 e 2007, constatou-se que dez empresas apresentaram acréscimo na sua pontuação final, enquanto sete apresentaram queda na sua pontuação final. Conclui-se, em relação ao nível de adequação da evidenciação social às recomendações da NBC T 15, com base na análise dos relatórios da administração e notas explicativas no período de 2005 a 2007 das 23 empresas de capital aberto do estudo, que há predomínio da classificação regular, pois quatro empresas obtiveram conceito insuficiente de evidenciação, doze conceito regular, seis conceito bom e uma empresa obteve conceito ótimo.